2021
DOI: 10.4274/jcrpe.galenos.2020.2021.0169
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency Prevalence in Late Neonatal Hypocalcemia: A Multicenter Study

Abstract: Objective: Late neonatal hypocalcemia (LNH) is a common metabolic problem associated with hypoparathyroidism, high phosphate intake and vitamin D deficiency, often presenting with seizures. In this cross-sectional study, we aimed to evaluate the role of vitamin D deficiency in LNH in Turkey and to describe the characteristics of affected newborns. Methods: Conducted with a cross-sectional design and with the participation of 61 neonatal centers from December 2015 to Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Among neonatal morbidities, hypocalcemia was significantly associated with neonatal vitamin D deficiency ( Table 3 and Table 4 ), consistent with previous studies [ 9 , 10 ]. A lower rate of respiratory illness was seen during SD than B-SD ( Table 1 ), but it was not related to neonatal vitamin D deficiency in the study ( Table 3 ), unlike previous reports [ 11 , 12 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Among neonatal morbidities, hypocalcemia was significantly associated with neonatal vitamin D deficiency ( Table 3 and Table 4 ), consistent with previous studies [ 9 , 10 ]. A lower rate of respiratory illness was seen during SD than B-SD ( Table 1 ), but it was not related to neonatal vitamin D deficiency in the study ( Table 3 ), unlike previous reports [ 11 , 12 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…Like previous studies, the results also showed that maternal vitamin D status could affect neonatal vitamin D levels, and maternal supplementation could improve the vitamin D level of the mother and her offspring [ 5 , 6 , 28 ]. Multiple roles of vitamin D in neonates have been reported besides its fundamental function in bone health, and its deficiency has been associated with many adverse health effects in neonates, including respiratory, infectious, and metabolic diseases [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Although more evidence on routine vitamin D supplementation to pregnant women is necessary, supplementation during pregnancy may help to reduce neonatal vitamin D deficiency without significant side effects [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation